Translation Analysis On Structural Shift Of Noun Phrases In The Land Of Five Towers Into Negeri 5 Menara By Ahmad Fuadi - Widyawati, Nurdiana Ita; , Dr. Anam Sutopo, S.Pd.,M.Hum (2016)
This research focuses on the translation analysis on structural shift of noun phrases in The Land of Five Towers novel. The objectives of this research are (1) to identify the structural shifts of the noun phrases found in The Land of Five Towers and its translation Negeri 5 Menara by Ahmad Fuadi and (2) to describe the accuracy of the translation on structural shift of noun phrases found in The Land of Five Towers translated into Negeri 5 Menara. This research belongs to descriptive qualitative research. The object of this research is the novel The Land of Five Towers and its translation. The data of this research are all information in the form of phrases found in The Land of Five Towers novel and its translation. There are 280 data in this study. The writer uses the documentation and questionnaire two raters in collecting data. The writer analyzes the data by comparing the source language and the source language refer to the data found to the theory. The result of this research shows that there are three types in translation of structural shift of noun phrasefound in The Land of Five Towers and its translation, as follows: NP1 translation of structural shift of noun phrases has 51 data or18,2%, NP2 translation of structural shift of noun phrase has 210data or 75% and NP3 translation of structural shift of noun phrases has 19 data or 6,8%.So, it finds 280 data or 100% in translation of structural shift of noun phrases in The Land of Five Towers novel and its translation. The accuracy of the data shows that there are 257 data or 91,8% belongs to the accurate translation accuracy. 19 data or 6,8% belongs to the less accurate translation accuracy. and 4 data or 1,4% belongs to the not accurate translation accuracy.